A biztonságtudatos vezetői attitűd vizsgálata - Juhász, Márta; Vasvári, Fanni (Vezetéstudomány / Budapest Management Review, 2022)
A safety culture is part of the organizational culture that defines the safety attitudes and behaviours of employees. The level of a safety culture is influenced by the role and commitment of the leader. Vernon Bradley’s tool, the Bradley Curve, shows where the safety culture and the attitude of the leader’s safety awareness in the organization are going. Four levels can be distinguished: The first, reactive stage can be equated with passive leadership. Managers in the second, dependent stage apply a strongly control-based, rule-following driving style in their workplace. In the third stage, safety is based on the emergence of individual-focused leadership. In the fourth stage of interdependence, managers prefer teamwork-based leadership in terms of safety awareness. In this study, the authors interviewed thirty-five managers of a high-risk organization, then used content analysis to determine how each manager feels about their own, subordinates’ and the overall organization’s security awareness.